MATHEMATICAL MODELING OF HUMAN LIFE - Борисов, Євген (SWorldJournal, 2025)
The paper considers the application of mathematical modeling to the social and philosophical spheres, in particular to human life. The work assumes that human life consists of opposing and at the same time interconnected concepts: happiness and unhappine